Studi Gaya Desain Perabot Ruang Makan Restoran Bon Ami di Surabaya - Grace Tanaya; Andereas Pandu Setiawan (Intra, 2013)
Bon Ami RestaurantSurabayais a building that exchange function from a house to a restaurant and it doesn’t change much in architectural and interior. This thesis aim to know, description of applying design style from its dining furniture. The research result shows that the restaurant furnitures have influence from baroque, art and craft, art nouveau, art deco.